Neutron Scattering of Aromatic and Aliphatic Liquids. Issue 13 (13th April 2016) - Falkowska, Marta; Bowron, Daniel T.; Manyar, Haresh G.; Hardacre, Christopher; Youngs, Tristan G. A.
Abstract: Organic solvents, such as cyclohexane, cyclohexene, methylcyclohexane, benzene and toluene, are widely used as both reagents and solvents in industrial processes. Despite the ubiquity of these liquids, the local structures that govern the chemical properties have not been studied extensively. Herein, we report neutron diffraction measurements on liquid cyclohexane, cyclohexene, methylcyclohexane, benzene and toluene at 298 K to obtain a detailed description of the local structure in these compounds. The radial distribution functions of the centres of the molecules, as well as the partial distribution functions for the double bond for cyclohexene and methyl group for methylcyclohexane and toluene have been calculated. Additionally, probability density functions and angular radial distribution functions were extracted to provide a full description of the local structure within the chosen liquids. Structural motifs are discussed and compared for all liquids, referring specifically to the functional group and aromaticity present in the different liquids. Abstract : Liquid refreshment : How does the presence of aromatic bonds or a methyl group influence the local ordering in liquids? To answer this question, five pure solvents (cyclohexane, cyclohexene, methylcyclohexane, benzene, and toluene) are studied by neutron scattering, obtaining information about the preferable separations, arrangement (see picture), and orientations between molecules in each liquid.